Philippine development plan 2011-2016. - Philippines. National Economic and Development Authority (Pasig City National Economic and Development Authority, 2011)
"The Philippine Development Plan 2011-2016 was formulated in accordance with the Constitutional provision of Section 9, Article VII, directing the Government?s economic and planning agency to "implement a continuing integrated and coordinated programs and policies for national development." Upon the assumption of President Benigno S. Aquino III of the country?s leadership, he embarked on his program of government that is based on his "Social Contract with the Filipino People" wherein he articulated a commitment to transformational leadership, institutional reform, economic stability and inclusive growth... The Philippine Development Plan provides a substantive translation of the Administration?s Social Contract. The support of all sectors of society will be crucial in turning our aspirations for a better quality of life for all Filipinos into reality."--Preface.
Chapter 1. In Pursuit of Inclusive Growth -- Chapter 2. Macroeconomic Policy -- Chapter 3. Competitive Industry and Services Sectors -- Chapter 4. Competitive and Sustainable Agriculture and Fisheries Sector -- Chapter 5. Accelerating Infrastructure Development -- Chapter 6. Towards a Resilient and Inclusive Financial System -- Chapter 7. Good Governance and the Rule of Law -- Chapter 8. Social Development -- Chapter 9. Peace and Security -- Chapter 10. Conservation, Protection and Rehabilitation of the Environment and Natural Resources.
Keywords: Philippines -- Economic policy -- 2011-2016.; Philippines -- Economic conditions; Philippines -- Social conditions